Assessment of the Water Quality Standard of Brahmani River in terms of Physico-Chemical Parameters - Kanungo, Swati; Bhuyan, Nirmal Kumar; Patra, Hemanta Kumar (International Journal of Scientific Research and Management (IJSRM), 2018)
The present investigation is aimed at assessing the current water quality standard along the stretch of Brahmani river in terms of physico-chemical parameters. In the selected study area, river Brahmani is receiving a considerable amount of industrial wastes and witnessing a considerable amount of human and agricultural activities .Nine samples were collected along the entire stretches of the river basin during the period from September-2013 to August-2014 on the first working day of every month. Various physico-chemical parameters like pH,, EC, total hardness, total alkalinity sodium, potassium, calcium, magnesium, nitrate, sulphate  D.O., B.O.D. etc. were analyzed. The present study indicates that the water quality of Brahmani river is well within tolerance limit taking the physico-chemical parameters into considerations.